BENEFITS OF ENGLISH TO SOCIETY - Sobirova Sevinch Sodiqjon qizi, (PEDAGOGS, 2025)
Abstract: English benefits society by opening doors to global communication, education, business, technology, and cultural exchange. It strengthens cooperation and empowers individuals and communities to grow in a connected world.